(untitled) (Eurasian Journal of Ecology, 2016)
P-selectin and actin cytoskeleton reorganization play an important role in vascular inflammation. In turn, there is increasing evidence that cerebrovascular factors contribute significantly to the development and progression of Alzhemer’s disease. In this study we have evaluated the effects of Aв42 oligomers on P-selectin expression and actin polymerization in mouse endothelial cells (bEnd3). Our results indicated that Aв42 induced plasma membrane accumulation of P-selectin and promoted actin polymerization, and these events were correlated with increased reactive oxygen species (ROS) generation. The rapid, posttranslational cell signaling response mediated by ROS may well represent an important physiological trigger of the microvascular inflammation in Alzheimer disease.